The Influence of Inducers on the Coltricia cinnamomea Laccase Activity and its Ability to Degrade POME - Subowo, Yohanes Bernard; Sugiharto, Arwan (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Some species of Basidiomycetes, specifically white rot groups, produce three ligninolytic enzymes, namely, Lignin Peroxidase (LiP), Manganese Peroxidase (MnP) and Laccase (Lac), which have low activity in degrading Palm Oil Mill Effluent (POME). The research objective was to obtain the data on the ability of the Coltricia cinnamomea to produce LiP, MnP, and Lac enzymes to degrade POME. This research also studied the effect of sucrose, alcohol, veratryl alcohol, CuSO4 and ZnSO4,as inducers. Isolates of Coltricia cinnamomea, which were stored in a PDA media at -20â„ƒ were obtained from the Microbiology section of the Research Center for Biology (LIPI). Furthermore, the growth media used were DM, Bean sprout Extract (TE) and PDB. The result indicated that PDB is the most suitable growth media for the production of ligninolytic enzymes, because in this medium these enzymes showed the highest activity. It was also observed that sucrose increased the laccase activity by 40.80%. Furthermore, Coltricia cinnamomea was able to reduce the concentration of Poly R-478 by 60.74%, after the addition of ZnSO4. In addition, it degraded and decreased the color and COD of POME, by 72.63% and 91.19% respectively, after the addition of veratryl alcohol, and incubation for 10 days. Therefore, this fungus can be used to degrade POME in order to prevent environmental pollution. Coltricia cinnamomea has not been used for POME degradation. By using Coltricia cinnamomea, weÂ obtained new data regarding the activity of laccase and its ability to degrade POME.Â